Estado, mercado e aplicativos over-the-top: o setor de telecomunicações e a construção da legitimidade participativa como forma de prevalência da regulação social - Pereira, Renan Farias (2019)
The development of a digital phase in society has triggered the need to analyze, question and, above all, reflect on social aspects related to its own organization, leading to changes in the behavior of individuals, the market and relations established between States. In view of this scenario, the world-wide network of computers made available new ways of acting before the "virtual society" and, among these performances in the cyberspace, the Over-the-Top (OTT Services) services are located. The objective of this research is to analyze the role of the regulatory State in relation to OTT services related to telecommunications, in order to allow the operation of several service provision centers, benefiting the market and establishing a range of equitable competitiveness for the consumer. In this logic, the project proposes to investigate the absence of regulation of Over-the-Top services - focusing on VoIP services, with the potential to develop competitive discrepancies in the market between such services and those already carrying out the same activity with obligations on the same. Research is justified because of a large number of global interconnections, which overcomes geographical, political and social barriers. Due to the emergence of these new technological information mechanisms, discussions aimed at analyzing the need for regulation appear more vigorously in order to harmonize the traditional telecommunications sectors and new virtual services, especially in a logic of fair competition. Therefore, the consumer is the end user of both services, the work becomes relevant from an economic and social point of view, especially since it is once again proposing the participation of society itself in the sectoral normative construction. From the legal point of view, it becomes relevant mainly because it brings new parameters for the regulation, commanded in the practical execution of the commands existing in the constitutional and infraconstitutional devices. In this prism, Legitimacy for Participation is built - based on the Luhmannian Theory of Systems - as a way of insertion of the society of processes involving the sectoral norm, starting from the assumption that as a final user of these services, it has relevant interest in the matter. Regarding the methodology, the systemic approach is used, mainly because the research relies on the construction of systematized thinking, through gradual evolutions that interconnect in order to produce a final result. Historical, comparative and functionalist methods are used as methods of procedure, with emphasis on the latter. Finally, it starts from the theoretical reference of the Luhmannian Systems Theory, verifying from Legitimation by the Procedure a way to trigger an economic-political-social regulation that provides the reduction of market failures and benefits of users of these services